Diasporic Consciousness: A Study of Identity Crisis in Jhumpa Lahiri’s “Unaccustomed Earth” - Dangwal, Kamlesh (Advances in Social Sciences Research Journal, 2024)
This paper explores the creative work of renowned diasporic Indian writer Jhumpa Lahari in her collection of eight short stories entitled "Unaccustomed Earth" where, she has explored the tug of war between the traditional-cultural values sustained by the immigrant parents but were curtailed by their precocious young American teenagers. The oscillation of permanent settlement in the new land and an overwhelming nostalgia for the homeland is a persistent theme of diasporic writers. In the introductory part of the research paper diaspora is defined and elucidated. The dispersion of Indian people across the globe and their vivid experiences and suffrages is discussed in the second part of the paper. The central themes of the diasporic writer and Indian diasporic writers and their closeness and corelation to celebrated diasporic writer Jhumpa Lahiri is discussed in the subsequent paragraphs. Diasporic terms like assimilation, adaptation, hybridity, host culture, ethnic and culture conflicts have been discussed in the light of the ‘Unaccustomed Earth’ by Lahiri. Irresistible past of the immigrants for their land of origin is a perennial source of study among diasporic writers. This paper explores the tug of war between the first-generation migrants who have the sense of rootlessness, alienation, and nostalgic homesickness on one hand and the hybrid and multicultural third generation and its synthesis of the past and the modern leading to socio-cultural, linguistic, and psychological transfusion widening new dimensions for the next generation in Lahiri’s stories.